Between consumerism and deconsumption − in search of a new model of society - Patrzałek, Wanda (Między konsumpcjonizmem a dekonsumpcją – w poszukiwaniu nowego modelu społeczeństwa, 2019)
The aim of this article is to present changes in consumption linked with deliberate limitations resulting from the assumption of a particular axionormative perspective, which is an outcome in the search for an innovative model of a consumer society based on the new culture of consumption. The discourse includes examples obtained by the author in the research conducted in 2018, using the method of triangulation applied to the data from a diagnostic survey of 504 respondents in the form of a questionnaire, and from 56 in-depth interviews (IDI) carried out in five voivodeships in Poland: Dolnośląskie, Łódzkie, Śląskie, Lubuskie and Opolskie. Based on the results of quantitative research, the author verified the proposed research hypotheses concerning the dependence of limiting consumption on the age, education, changes in the levels of income, etc., whereas the qualitative research allowed to determine the motives prompting consumers to limit consumption. The theoretical basis of the conducted analyses was provided by the macro-sociological theories of the consumer society, and the latest trends in consumption based on the processes of deconsumption, pro-health and ethical consumption, as well as retro consumption
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 221-234